Evaluation of clinical competence and its related factors among ICU nurses in Kermanshah-Iran: A cross-sectional study - Azam Faraji; Mahtab Karimi; Seyyed Mohsen Azizi; Maryam Janatolmakan; Alireza Khatony (Elsevier, 2019)
Objectives: The present study was conducted to evaluate the clinical competence and its related demographic factors among critical care nurses in Kermanshah, Iran. Methods: In this cross-sectional study, 155 Iranian nurses were selected by stratified random sampling. The data collection tools included a personal information form and the "Nurse Competence Scale". Data were analyzed using descriptive and analytical statistics. Results: The mean score of nurses' clinical competence was equal to 76.14 ± 1.59 out of 100, which was at a "very good level". The mean score of using clinical competence in practice was equal to 70.38 ± 15.25 out of 100, which was at a "good level". Among the subscales of clinical competence, the highest mean score was related to "managing situation". The mean score of "using clinical competence in practice" was related to the subscale of "therapeutic interventions". There was no statistically significant difference among the score of clinical competence of nurses varying with different gender, age, academic degree, and work experience. Conclusions: The clinical competence of critical care nurses in Kermanshah was at a "very good" level, and the use of clinical competence in practice was at a "good level." Given the importance of clinical competencies in practice, nurses' clinical competence should be evaluated objectively and positive measures should be taken to promote the application of their clinical competence. Keywords: Clinical competence, Intensive care units, Nurses, Personal characteristics